Soil physical properties in ‘Royal Gala’ apple orchards under conventional and organic production systems (Revista de Ciências Agroveterinárias, 2012)
The management of apple orchards is conditioned by the form of cultivation adopted, which influences on plant yield, profitability and longevity of the area. This study aimed to evaluate the effects of management systems for conventional and organic apple production on soil physical properties and identify the variables that discriminate between the two production systems, using canonical discriminant analysis (CDA). The experiment was carried out in São Joaquim, SC, in two orchards, one under conventional system (CS) and the other under organic system (OS), both established in 2001, using Royal Gala cultivar, on M9 rootstock, in a Humic Cambisol. Soil samples were collected during 2008-2009 season in the layers 0-10 cm and 10-20 cm. The soil physical properties evaluated were particle size distribution, aggregate stability, represented by the mean geometric diameter (MGD), bulk density (BD), total porosity (TP) and degree of flocculation (DF). The results were tested for comparison of means and CDA. The OS had higher values of MGD and BD in the two layers. In the 10-20 cm layer, macroporosity was greater in the CS. The MGD in the layer 0-10 cm and microporosity in the layer 10-20 cm showed the highest values of parallel discrimination rate coefficient (PDRC), revealing that these properties were good indicators of soil physical quality and can be used to study changes in apple production caused by the production systems.
Keywords: Malus domestica (Borkh); Production systems; Soil physics; Canonical discriminant analysis.